1998
DOI: 10.1080/014311698214037
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory experiment, field and remotely sensed data analysis for the assessment of suspended solids concentration and secchi depth of the reservoir surface water

Abstract: To cite this article: V. K CHOUBEY (1998) Laboratory experiment, field and remotely sensed data analysis for the assessment of suspended solids concentration and secchi depth of the reservoir surface water, International

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The data of in situ measurements shows positive correlations between DN and TSS with R and Root Mean Squared (RMS) values were 0.9256 and 3.6237 mg/I respectively. Such characteristics were also observed by other investigators using remote sensing data in the visible channel for suspended sediment studies (Choubey, 1998). Figure 5 depicted higher concentrations of Total Suspended Solids were distributed near the river mouths and the shallow at the southern region of the channel.…”
Section: Remote Sensing-gis In Monitoring Water Quality In Malaysiasupporting
confidence: 65%
“…The data of in situ measurements shows positive correlations between DN and TSS with R and Root Mean Squared (RMS) values were 0.9256 and 3.6237 mg/I respectively. Such characteristics were also observed by other investigators using remote sensing data in the visible channel for suspended sediment studies (Choubey, 1998). Figure 5 depicted higher concentrations of Total Suspended Solids were distributed near the river mouths and the shallow at the southern region of the channel.…”
Section: Remote Sensing-gis In Monitoring Water Quality In Malaysiasupporting
confidence: 65%
“…The results were satisfactory (R 2 = 0.82) for turbidity, however, poor for TSS (R 2 = 0.45). There are several reasons for the poor estimated TSS relations, including the various types and grain sizes of sediment, [ 58 , 59 ]. Gin et al [ 58 ] studied the spectral reflectance of water containing concentrations of organic and inorganic sediments isolated under controlled experimental conditions and natural sunlight.…”
Section: Resultsmentioning
confidence: 99%
“…All of these approaches result in robust statistical relationships between satellite‐derived reflectance and ground‐based SSC or turbidity data, with coefficients of determination (r 2 ) ranging from 0.60 to 0.99. Principle sources of uncertainty in these relationships result from differences in sediment color, grain size, and mineralogy within a study region [ Choubey , 1998; Novo et al , 1989; Han and Rundquist , 1996], from bottom reflectance in shallow areas where suspended sediment concentrations are less than 100 mg/L [ Tolk et al , 2000], from contamination by chlorophyll, carotenoids, and other reflective suspended or dissolved material [ Tassan , 1994; Quibell , 1991; Han , 1997], and from differences in atmospheric correction techniques [ Stumpf and Pennock , 1989]. Additionally, in regions with SSC values greater than 250 mg/L some studies have found that reflectance begins to saturate and that the SSC‐reflectance relationship becomes logarithmic [ Ritchie and Cooper , 1988; Ritchie et al , 2003].…”
Section: Remote Sensing Of Suspended Sediment Concentration In Freshwmentioning
confidence: 99%